Role of the Anaphase-Promoting Complex Activator Cdh1 in the Virulence of Cryptococcus neoformans - Qiu-Hong Liao; Lian-Tao Han; Meng-Ru Guo; Cheng-Li Fan; Tong-Bao Liu (Journal of Fungi)
Cryptococcus neoformans is a globally distributed human fungal pathogen that can cause cryptococcal meningitis with high morbidity and mortality. In this study, we identified an anaphase-promoting complex (APC) activator, Cdh1, and examined its impact on the virulence of C. neoformans. Our subcellular localization analysis revealed that Cdh1 is situated in the nucleus of C. neoformans. Disrupting or overexpressing the CDH1 gene caused abnormal capsule formation in C. neoformans. The cdh1Δ mutant displayed slight sensitivity when grown at 37 °C, indicating that Cdh1 plays a role in maintaining the growth of C. neoformans at 37 °C. A fungal virulence assay showed that Cdh1 is closely associated with the virulence of C. neoformans, and both the cdh1Δ mutant and CDH1OE overexpression strains significantly diminished the virulence of C. neoformans. The Cryptococcus–macrophage interaction assay revealed that both the cdh1∆ mutant and the CDH1OE strains had significantly lower proliferation ability inside macrophages. Furthermore, the infection of the cdh1Δ mutant significantly activated neutrophil recruitment, as well as Th2 and Th17 immune responses, in lung tissue. In summary, our findings indicate that Cdh1 is crucial for producing virulence factors and fungal virulence in C. neoformans. The findings of this study can offer valuable insights and form the basis for further study of the regulatory mechanisms governing the pathogenicity of C. neoformans, potentially leading to the development of novel therapeutic strategies.